2019
DOI: 10.1101/756858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated annotations and analyses of small RNA-producing loci from 47 diverse plants

Abstract: 22Plant endogenous small RNAs (sRNAs) are important regulators of gene expression. 23There are two broad categories of plant sRNAs: microRNAs (miRNAs) and endogenous short 24interfering RNAs (siRNAs). MicroRNA loci are relatively well-annotated but comprise only a 25 small minority of the total sRNA pool; siRNA locus annotations have lagged far behind. Here, we 26 used a large dataset of published and newly generated sRNA sequencing data (1,333 sRNA-seq 27 libraries containing over 20 billion reads) and a unif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 105 publications
3
42
1
Order By: Relevance
“…Consistent with previous analysis of sRNAs in soybean (Arikit et al, 2014;Lunardon et al, 2020), the majority of siRNA loci in soybean features 24-nt siRNAs, but 21-and 22-nt loci demonstrated higher sRNA abundances ( Figure 2B). In wild-type libraries, our analysis identified 1,304 22-nt siRNA loci from the seed coat and 1,371 from leaf sample, which accounted for only ~3% of the total number of loci but over 20% of total siRNA abundance ( Figure 2B).…”
Section: Impacts Of Dcl2 Loss-of-function On Srna Biogenesis In Soybeansupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous analysis of sRNAs in soybean (Arikit et al, 2014;Lunardon et al, 2020), the majority of siRNA loci in soybean features 24-nt siRNAs, but 21-and 22-nt loci demonstrated higher sRNA abundances ( Figure 2B). In wild-type libraries, our analysis identified 1,304 22-nt siRNA loci from the seed coat and 1,371 from leaf sample, which accounted for only ~3% of the total number of loci but over 20% of total siRNA abundance ( Figure 2B).…”
Section: Impacts Of Dcl2 Loss-of-function On Srna Biogenesis In Soybeansupporting
confidence: 91%
“…These 22-mers are capable of triggering the production of secondary 21-nt siRNAs to further silence TEs or protein-coding genes. A recent study of sRNAs from 47 diverse plant species showed that many major crops and vegetables produce 22-nt siRNAs at much higher levels compared to Arabidopsis (Lunardon et al, 2020). Our results here demonstrated that DCL2-dependent 22-nt siRNAs are capable of regulating natural traits, and future investigation in more species could help to expand our understanding about the possibly underappreciated function of 22-nt siRNAs in wild-type plants.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…1; [43, 46]). Using miR825-5p to search for potential target genes in the B. oleareacea genome in a recently created web browser (https://plantsmallrnagenes.science.psu.edu/ ; [77]), we found that several of its predicted targets, which display sequence similarity to Arabidopsis TNL genes, do accumulate significant amounts of 21 nt siRNAs, supporting the potential conservation of miR825-5p TNL regulatory network among Brassicaceae ( Fig. S3 ).…”
Section: Discussionmentioning
confidence: 54%